Determination of Nitrite Through S-Nitrosocaptopril Formation and Fluorescent Derivatization of Remaining Captopril Using o-Phthalaldehyde and Glycine. (4th March 2019) - Li, Youxin; Zhang, Ying; al-karim Ali, Abd; Danielson, Neil D.
Abstract: We have developed an indirect fluorescence method for the determination of nitrite based on two reactions. The S -nitrosocaptopril produced by the first reaction between nitrite and excess captopril is not fluorescent. The fluorescent product produced by the residual captopril with glycine and o -phthalaldehyde is then measured and related to the nitrite concentration. We have optimized comprehensively the reaction condition parameters, including the thiol regent for the two reactions, reaction temperature and pH value for the first reaction, and the choice of amino acid, pH value, the ratio of reactants, buffer concentration, reaction temperature, and time for the second fluorescence reaction. Potential interferences by 8 cations and 10 anions on the fluorescence intensity were slight except for iodate and periodate which could likely be removed by addition of a reducing agent. For the analytical figures of merit, the limits of detection and quantitation of nitrite are 0.8 and 2.5 nM, respectively. The fluorescence intensity is found to linearly decrease with increasing nitrite from 0 to 140 nM. The method has shown to have good interday (<8%) and intraday precision (1–4%). The formation of nitrite from nitrate due to microbial degradation of spinach can be easily followed. Although the method requires a two-step reaction sequence that takes a significant analysis time, the safety and cost of the reagents (no carcinogenic amino naphthalene compounds) as well as excellent analytical figures of merit are significant advantages.